Creative Arts and Experiences in Palliative Care - Maria José dos Santos Cunha; Capelas, Manuel Luís (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this article, we present a work developed with palliative patients with the aim of, through art, enabling them to find answers that would help them overcome situations that kept them involved in thoughts, fears, and anxiety that consumed their energy, joy, and will to live. For this purpose, we used a qualitative methodology —research-action— and the attained results revealed how arts can be useful to these patients by providing them, through the work they have developed, with an improvement in self-esteem, disposition, and well-being in disease avoidance and the expression and communication of emotions.